Isotopic composition of Conomurex fasciatus shells as an environmental proxy for the Red Sea. (5th January 2017) - Hausmann, N.; Colonese, A.C.; de Lima Ponzoni, A.; Hancock, Y.; Meredith-Williams, M.; Leng, M.J.; Bailey, G.N.
Abstract: The marine gastropod Conomurex fasciatus (Born 1778) is the main component of thousands of shell middens on the Farasan Islands in the southern Red Sea. The middens date from 6500 to 4500 cal BP and cover the period of increased aridification over the region. No general research on C. fasciatus has been carried out before and basic information about the species is mostly speculative. To test if C. fasciatus shells can be used as a recorder of climate variability, we collected living specimens from the Farasan Islands, in Saudi Arabia, over a 1.5 year period. This area receives almost no precipitation and sea surface salinity is extremely high (38–39 psu), and sea surface temperature (SST) ranges from +26.5 °C to +34.9 °C. Raman spectroscopy results on modern C . fasciatus shell samples show these specimens to be aragonitic. Ground fragments from archaeological C . fasciatus shells used for isotope analyses were also measured by Raman spectroscopy and shown to be well preserved against diagenetic alterations leading to aragonite to calcite transformation. Measured shell-edge δ 18 O values range from −0.5‰ to −1.7‰. Calculated modern shell edge temperatures from these δ 18 O values correlate with modern SST measured on site with an error of ±2.4 °C. Two different growth rates occurred in the shells of C. fasciatus . The measurement of growth increments in the lip part of adult specimens indicates a tide-related growth rate of ∼13 mm/year. Sequential δ 18 O data from juvenile parts of the shell indicates a faster growth rate of ∼90 mm/year. This growth rate and the correlation of δ 18 O with measured temperatures allows the use of C. fasciatus shell δ 18 O as a palaeoclimate proxy.